Pengaruh Kualitas Pelayanan dan Persepsi Kemudahan terhadap Keputusan Pembelian Jasa Agen BRILink Gratia di Kecamatan Nita Kabupaten Sikka - Yulius Laba; Antonius P. Kurniawan; Nunsio H.Meylano (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This study aimend to (1) determine the effect of service quality on purchasing decisions for BRILink Gratia agent services in Nita sub-district, Sikka Regency. (2) determine the effect of perceived convenience on purchasing decisions for BRILink Gratia agent services in Nita sub-district, Sikka Regency. (3) to determine the effect of services quality and perceived convenience on purchasing decisions for BRILink Gratia agent services in Nita sub-district, Sikka Regency. In this study, the research design used descriptive with a quantitative approach. In this study, the sample size taken using the formula amounted to 96 respondents from BRILink Gratia customers. Data was collected through questionnaires and analyzed using inferential statistics, namely multiple linear regressions. Hypothesis testing was done through the T test and F test. The results of this study indicated that : (1) that partially the service quality variable (X1) had a significant effect on the service purchase decision variable (Y) with a t value of 3.042 > 1.98 (2) partially the perceived convenience variable (X2) had a significant effect on the service purchase decision variable (Y) with a t value of 2.320 > 1.98 (3) together the two independent variables, namely the service quality variable (X1) and perceived convenience (X2) have a significant effect on service purchase decisions (Y). with an F table value of 19.971 > 3.09